Implementation of Entrepreneurship Learning in the Production Unit as a Process of Internalizing the Characters of Never Give Up and Persistence At State Vocational High School 1 Malinau - Mahdiansyah Mahdiansyah; Denies Priantinah (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
This study aims to analyze the level of understanding and awareness, identify and evaluate, assess the gap between the designed entrepreneurship learning objectives and evaluate the level of mentoring and supervision provided by teachers or mentors in supporting the internalization of the character of never giving up and being persistent through production unit activities at SMK Negeri 1 Malinau. The research method used in this study is a descriptive qualitative approach. The results of this study indicate that the level of understanding and awareness of students can increase their awareness and readiness to face challenges in the world of work, according to their field of expertise. The implementation of the values ​​of never giving up and tenacity in entrepreneurship learning at SMK plays a crucial role in developing various important aspects in students. The gap between the objectives of entrepreneurship learning and its implementation, namely limited learning time, lack of adequate facilities and practical tools, and minimal training for teachers, hinder students from internalizing these values ​​effectively. With a combination of active teacher roles and effective supervision, students are encouraged to continue trying despite difficulties, thus supporting the development of a resilient character and being ready to face challenges in the world of entrepreneurship